The Effects of Early Intervention on Social Communication Outcomes for Children with Autism Spectrum Disorder: A Meta-analysis - Fuller, Elizabeth A.; Kaiser, Ann P. (Journal of autism and developmental disorders, 2020)
This meta-analysis examined the effects of early interventions on social communication outcomes for young children with autism spectrum disorder. A systematic review of the literature included 1442 children (mean age 3.55 years) across 29 studies. The overall effect size of intervention on social communication outcomes was significant ( g = 0.36). The age of the participants was related to the treatment effect size on social communication outcomes, with maximum benefits occurring at age 3.81 years. Results did not differ significantly depending on the person implementing the intervention. However, significantly larger effect sizes were observed in studies with context-bound outcome measures. The findings of this meta-analysis highlight the need for further research examining specific components of interventions associated with greater and more generalized gains.